Current situation of rapid multiplication techniques for early generation seed potato production in Sub-Saharan Africa - Harahagazwe, D.; Andrade-Piedra, J.L.; Parker, M.; Schulte-Geldermann, Elmar (International Potato Center, 2018)
The potato crop is increasingly becoming one of the top food crops in sub-Saharan Africa (SSA) in terms of production, regional trade, and consumption. However, potato growers (mainly smallholder farmers) still face many challenges that cause huge yield gaps with direct impact on their livelihoods and income. It is common knowledge that the major driver for these yield losses is seed degeneration and poor dissemination of improved varieties. In this study we assess the current situation in the production of early generation seed (EGS) potato to understand critical problems that limit the efficiency of technologies used. The survey was conducted in seven SSA countries (Burundi, Ethiopia, Kenya, Malawi, Rwanda, Tanzania, and Uganda) from November to December 2017. It consisted of site visits, face-to-face interviews, secondary information, and information exchange through various communication platforms. This paper provides insights on the principal actors in producing in vitro plantlets, cuttings, and minitubers, with emphasis on the technologies used, the production capacity in place, and challenges. One of the key findings is that the total production of minitubers in the seven countries increased tenfold from 2008 to 2017. In this regard, Kenya and Rwanda turn out to be the major investors and producers of EGS potato in SSA. Schematic representations are used to depict the organizational structures of national formal seed systems. Rapid multiplication techniques used, including aeroponics, hydroponics, and rooted apical cuttings, are described and their comparative advantages to the conventional technique outlined. We also provide an overview on the germplasm used in seed systems, with a special focus on end-users' preferences. The paper also provides contextualized suggestions on how to improve the efficiency of the seed systems analyzed.